Music Aesthetics and Mental Health: A Narrative Review of Concepts, Evidence, and Contexts - Algristian , Hafid (Harmonia : Journal of Music and Arts, 2024)
The aesthetic dimensions of music have attracted increasing scholarly attention due to their potential to enhance psychological well-being. This narrative review aimed to synthesize conceptual, empirical, and contextual perspectives on music aesthetics and mental health. Literature was collected from major academic databases, including Scopus, Web of Science, and PubMed, using keywords such as aesthetic appeal, music therapy, emotion in music, and mental health. Inclusion criteria focused on peer-reviewed studies addressing the relationship between music and psychological outcomes, while exclusion criteria removed works unrelated to aesthetics or lacking empirical grounding. Both qualitative and quantitative studies were included to ensure breadth and depth. Findings revealed diverse conceptual frameworks, ranging from psychological and historical analyses to therapeutic models and cross-cultural interpretations. Empirical evidence demonstrated significant improvements in mental health outcomes associated with music engagement, with statistical data confirming the benefits of both active creation and passive appreciation. Paradoxically, even sad music was found to generate pleasurable and beneficial experiences, reflecting the complexity of emotional responses. Cross-national studies highlighted cultural variability, showing that aesthetic experiences are deeply shaped by social, economic, and institutional contexts. The discussion linked these findings to systemic barriers, emphasizing the need for more inclusive methodologies, cross-cultural research, and policy frameworks that support equitable access to aesthetic practices. Overall, the review confirms the therapeutic and social significance of music aesthetics while calling for greater inclusivity, methodological innovation, and systemic support. These findings suggest that advancing music aesthetics in research, education, and health services represents a crucial strategy for fostering psychological resilience and social cohesion.